2021
DOI: 10.3390/ijfs9010007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatility Volume and Open Interest for Nifty Index Futures Using GARCH Analysis and VAR Model

Abstract: The generalized autoregressive conditional heteroscedastic model (GARCH) is used to estimate volatility for Nifty Index futures on day trades. The purpose is to find out if a contemporaneous or causal relation exists between volatility volume and open interest for Nifty Index futures traded on the National Stock Exchange of India, and the extent and direction of these relationships. A complete absence of bidirectional causality in any particular instance depicts noise trading and empirical analysis according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Physica A 505, 2018, 632-47 Some studies have found that globally oriented companies with exposure to China have seen their shares decline, while companies in the natural gas, software, food and healthcare sectors in America have performed positively during the Covid-19 pandemic. 9 Another study showed that the South Korean stock market was more resilient than the French stock market during the pandemic. 10 Charfeddine used GARCH to analyze the volatility of stock indices during the Covid-19 pandemic.…”
Section: Stock Markets Analysts During Period Of Covid -19mentioning
confidence: 99%
“…Physica A 505, 2018, 632-47 Some studies have found that globally oriented companies with exposure to China have seen their shares decline, while companies in the natural gas, software, food and healthcare sectors in America have performed positively during the Covid-19 pandemic. 9 Another study showed that the South Korean stock market was more resilient than the French stock market during the pandemic. 10 Charfeddine used GARCH to analyze the volatility of stock indices during the Covid-19 pandemic.…”
Section: Stock Markets Analysts During Period Of Covid -19mentioning
confidence: 99%
“…To have a non-spurious estimate of this relationship in a non-stationary statistical universe, it is recommended to first resort to a protocol of preliminary statistical tests (Spurious regression is a situation in which using nonstationary time series in linear regression shows erroneous results). First, we must determine the order of integration of the variables [10]. Considering the importance of this step thereafter, one must resort to different stationarity tests: the usual Dickey-Fuller unit root test (ADF).…”
Section: Study Of Stationaritymentioning
confidence: 99%
“…Extremely low VIX levels might indicate complacency and potential market overheating, however extremely high levels might suggest a market bottom is approaching. Following this general rule, investors can avoid some potential risks and receive a higher return [5].…”
Section: Introductionmentioning
confidence: 99%